The Influence of Message Framing and Issue Involvement - Maheswaran, Durairaj; Meyers-Levy, Joan (Journal of Marketing Research, 1990)
Studies examining message framing effects on persuasion have produced mixed results. Some studies show positively framed messages, which specify attributes or benefits gained by using a product, to be more persuasive than negatively framed messages, which specify attributes or benefits lost by not using a product. Reverse outcomes have been obtained in other studies. The authors explore a theoretical explanation for such findings by investigating whether differences in the degree to which people engage in detailed message processing account for the mixed results. The findings support the view that positively framed messages may be more persuasive when there is little emphasis on detailed processing, but negatively framed messages may be more persuasive when detailed processing is emphasized.